Comparison of Participants' Behaviors During Telepractice and In-Person Family-Centered Early Intervention: An Exploratory Study. Issue 3 (July 2022) - McCarthy, Melissa; Leigh, Greg; Arthur-Kelly, Michael
Abstract : Family-centered early intervention (FCEI) is characterized by the collaborative relationships that exist within triads of practitioners, caregivers, and young children whereby practitioners use capacity-building practices to foster caregivers' involvement in supporting their children's early development. Traditionally, FCEI has been provided in-person with practitioners and families physically present in the same location but, for children who are deaf or hard of hearing, access to in-person early intervention is often limited by external factors. To address these challenges, practitioners are using telepractice more frequently to connect with families through synchronous, 2-way videoconferencing. This exploratory study examined whether participants' behaviors differed when FCEI was delivered in-person and through telepractice. The Triadic Intervention and Evaluation Rating Scale (TIERS) was used to compare 2 groups of triads (16 in-person and 12 telepractice) in terms of practitioner behaviors, caregiver behaviors, and the reciprocal influences of those behaviors. Results indicated that practitioners in telepractice used most family-centered practices more frequently than practitioners in-person. Correspondingly, caregivers in telepractice had more opportunities to participate in early intervention and more frequently demonstrated a variety of participation behaviors than caregivers in-person. Although further research is required to confirm these exploratory findings, these results suggest that FCEI provided through telepractice may enhance practitioners' use of family-centered practices, which, in turn, supports greater participation by caregivers.